The geometric effect of an off-centered cross-section on nickel-titanium rotary instruments: A finite element analysis study - Jung-Hong Ha; Sang Won Kwak; Antheunis Versluis; Chan-Joo Lee; Se-Hee Park; Hyeon-Cheol Kim (Elsevier, 2017)
Background/purpose: Geometric design dictates the mechanical performance of nickel-titanium rotary instruments. Using finite element (FE) analysis, this study evaluated the effects of an off-centered cross-sectional design on the stiffness and stress distribution of nickel-titanium rotary instruments. Materials and methods: We constructed three-dimensional FE models, using ProTaper-NEXT type design (PTN) as well as three other virtual instruments with varied cross-sectional aspect ratios but all with the same cross-sectional area. The cross-sectional aspect ratio of the PTN was 0.75, while others were assigned to have ratios of 1.0 (square), 1.5 (rectangle), and 2.215 (centered-rectangle). The PTN center of the cross-section was 'k', while others were designed to have 0.9992k, 0.7k, and 0 for the square, rectangle, and centered-rectangle models, respectively. To compare the stiffness of the four FE models, we numerically analyzed their mechanical response under bending and torque. Results: Under the bending condition, the square model was found to be the stiffest, followed by the PTN, rectangle, and then the centered-rectangle model. Under the torsion, the square model had the smallest distortion angle, while the rectangular model had the highest distortion angle. Conclusion: Under the limitation of this study, the PTN type off-centered cross-sectional design appeared the most optimal configuration among the tested designs for high bending stiffness with cutting efficiency while rotational stiffness remained similar with the other designs.